This box with cedar nuts from Irkuts was brought back from Russia around 1970 by Maarten Biesheuvel and his wife for Karel van het Reve. Roasted cedar nuts that Andrej Amalrik sent from Siberia to Pavel Litvinov. Enclosed the original letter to Van het Reve and his wife
This box with cedar nuts from Irkuts was brought back from Russia around 1970 by Maarten Biesheuvel and his wife for Karel van het Reve. Roasted cedar nuts that Andrej Amalrik sent from Siberia to Pavel Litvinov. Enclosed the original letter to Van het Reve and his wife.